Alternative Carbon Sources for Isoprene Emission. (December 2018) - de Souza, Vinícius Fernandes; Niinemets, Ülo; Rasulov, Bahtijor; Vickers, Claudia E.; Duvoisin Júnior, Sergio; Araújo, Wagner L.; Gonçalves, José Francisco de Carvalho
Abstract : Isoprene and other plastidial isoprenoids are produced primarily from recently assimilated photosynthates via the 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway. However, when environmental conditions limit photosynthesis, a fraction of carbon for MEP pathway can come from extrachloroplastic sources. The flow of extrachloroplastic carbon depends on the species and on leaf developmental and environmental conditions. The exchange of common phosphorylated intermediates between the MEP pathway and other metabolic pathways can occur via plastidic phosphate translocators. C1 and C2 carbon intermediates can contribute to chloroplastic metabolism, including photosynthesis and isoprenoid synthesis. Integration of these metabolic processes provide an example of metabolic flexibility, and results in the synthesis of primary metabolites for plant growth and secondary metabolites for plant defense, allowing effective use of environmental resources under multiple stresses. Highlights: The high emission rates of isoprene under conditions of restricted photosynthesis can be associated with an increase in the availability of alternative carbon sources for the MEP pathway. The proposed shunt of carbon around the Calvin–Benson cycle involving glucose-6 phosphate could, at least partly, explain the incomplete 13 C labeling of isoprene, which so far has been interpreted as uncoupling between isoprene and photosynthetic metabolism. The differences in the isoprene emission rate at different leaf developmental stages are related to overall changes in carbon partitioning between isoprenoid synthesis and primary metabolic pathways, and within the isoprenoid synthesis pathway, to dimethylallyl diphosphate (DMADP) by isoprene synthase and downstream prenyltransferase reactions. Limited availability of energetic cofactors and reducing equivalents can inhibit MEP pathway flux, resulting in an accumulation of MEP pathway intermediates and decreased carbon availability for isoprene production.